Development of a Smart Business Framework Based on Artificial Intelligence and Sustainability - Arya Mawla Kamakshi (IHSA Institute, 2025)
The rapid advancement of Artificial Intelligence (AI) and digital technologies has transformed business operations, enabling organizations to enhance efficiency, innovation, and data-driven decision-making. At the same time, increasing stakeholder expectations and global sustainability agendas have highlighted the importance of integrating environmental, social, and governance (ESG) principles into business strategies to achieve long-term competitiveness. However, existing studies often examine AI adoption and sustainability independently, creating a need for a unified Smart Business Framework that combines AI capabilities with sustainability principles. Therefore, this study aims to develop and validate a Smart Business Framework based on Artificial Intelligence and Sustainability. The research employed the Design Science Research (DSR) methodology, supported by a systematic literature review of publications indexed in major scientific databases between 2020 and 2026 and expert validation using a modified Delphi approach. The framework was constructed by synthesizing key concepts from previous studies and subsequently refined through expert evaluation to ensure its theoretical robustness and practical applicability. The results propose a comprehensive framework integrating Artificial Intelligence capability, Digital Transformation, Business Intelligence, Innovation, Governance, Sustainability, Customer Value, and Business Performance into a unified strategic architecture for intelligent and sustainable business transformation. The proposed framework contributes to Smart Business literature by integrating previously fragmented research streams while providing managers and policymakers with practical guidance for implementing responsible AI, promoting sustainable digital transformation, and strengthening organizational competitiveness. Furthermore, the framework establishes a solid foundation for future empirical studies examining AI-driven sustainable business development across various industries and organizational contexts.